MODEL PEMBELAJARAN GEOMETRI MENGGUNAKAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) DI SEKOLAH DASAR - Syafri Ahmad; Mohamad Bin Bilal Ali (Pedagogi: Jurnal Ilmu Pendidikan, 2016)
The phenomenon that often occurs in elementary school geometry teacher in the real world do not associate with students. Learning in the classroom is teacher-centered. The purpose of this study is to develop learning model geometry using realistic mathematics education approach (PMRI) are valid, practical, and effective. In addition, it also aims to see the difference between the students' learning outcomes geometry before and after using model geometry approach PMRI. This study was a research and development (R & D). For field trials used an experimental research design time series one-group pretest and posttest. Subjects were students in public elementary school no.14 Parak Laweh Padang four grade. The results showed that the learning model geometry with PMRI approaches that have been developed, as well as through experimental trials have been valid, practical, and effective. In sefesific there are differences in geometry student learning outcomes significantly between before and after using model geometry with PMRI approach. To the elementary school teacher suggested in learning geometry using learning model geometry PMRIapproach